2017
DOI: 10.1002/anie.201707191
|View full text |Cite
|
Sign up to set email alerts
|

Effector‐Triggered Self‐Replication in Coupled Subsystems

Abstract: In living systems processes like genome duplication and cell division are carefully synchronized through subsystem coupling. If we are to create life de novo, similar control over essential processes such as self-replication need to be developed. Here we report that coupling two dynamic combinatorial subsystems, featuring two separate building blocks, enables effector-mediated control over self-replication. The subsystem based on the first building block shows only self-replication, whereas that based on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Ag ood understanding of the requirements for self-replicationn ow exists [2] and severalchemical self-replicatings ystems have been reported. [2,3] Also, the emergence of self-replicators from relatively complex mixtures (in particulard ynamic combinatorial libraries, DCLs) [4] has been described by Philp [5] and by us. [6] We previously developed DCLs using building blocks equippedw ith two thiol groups that can oxidize to form disulfide macrocycles which continuously exchange buildingb locks through reversible disulfide exchange reactions.…”
mentioning
confidence: 99%
“…Ag ood understanding of the requirements for self-replicationn ow exists [2] and severalchemical self-replicatings ystems have been reported. [2,3] Also, the emergence of self-replicators from relatively complex mixtures (in particulard ynamic combinatorial libraries, DCLs) [4] has been described by Philp [5] and by us. [6] We previously developed DCLs using building blocks equippedw ith two thiol groups that can oxidize to form disulfide macrocycles which continuously exchange buildingb locks through reversible disulfide exchange reactions.…”
mentioning
confidence: 99%
“…The dissimilar behaviour of s when they are alone or mixed with other species allowed the group to design a library that shows no replication until an effector is present. 61 In this particular case, a BB capable of selfreplication and a known to form a receptor in the presence of a template were combined together. In the absence of template, no self-catalysis is detected and the different components form mixed structures.…”
Section: Dynamic Covalent Chemistry In Complex Systemsmentioning
confidence: 99%
“…[44] Using an attached dithiol moiety, the pentapeptides can assemble into mixtures of macrocyclic oligomers of different sizes through disulfide bond formation. [46] Most recently, Sadwonik et al reported real time diversification of competing self-replicating molecules into two sets of replicators, with one the descendant of the other. Mechanical stimulation causes exponential growth from both sides of the hexameric macrocycles and the formation of fibers.…”
Section: Self-replicating Peptidesmentioning
confidence: 99%
“…In later work, the Otto group investigated the impact of amino acid sequence variations on the properties of self-selected replicators [45] and identified replicator systems that can be controlled via an external effector. [46] Most recently, Sadwonik et al reported real time diversification of competing self-replicating molecules into two sets of replicators, with one the descendant of the other. [47] Despite competing for the same two essential building blocks, the new replicators manage to coexist through modest specialization on one of two feedstock molecules.…”
Section: Self-replicating Peptidesmentioning
confidence: 99%